2017
DOI: 10.3389/fphar.2017.00084
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Immature Orange (Aurantii fructus immaturus) and Citrus Unshiu Peel (Citri unshiu pericarpium) Induce P-Glycoprotein and Cytochrome P450 3A4 Expression via Upregulation of Pregnane X Receptor

Abstract: P-glycoprotein (P-gp) and cytochrome P450 3A4 (CYP3A4) are expressed in the intestine and are associated with drug absorption and metabolism. Pregnane X receptor (PXR) is the key molecule that regulates the expression of P-gp and CYP3A4. Given that PXR activity is regulated by a variety of compounds, it is possible that unknown PXR activators exist among known medicines. Kampo is a Japanese traditional medicine composed of various natural compounds. In particular, immature orange [Aurantii fructus immaturus (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Okada et al . () have shown that an ethanol extract of bitter orange (dried immature fruit) induced expression of cytochrome CYP3A4 and P‐glycoprotein in LS180 cells in culture by upregulating pregnane X receptor. Naringin and narirutin were the primary constituents of the extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okada et al . () have shown that an ethanol extract of bitter orange (dried immature fruit) induced expression of cytochrome CYP3A4 and P‐glycoprotein in LS180 cells in culture by upregulating pregnane X receptor. Naringin and narirutin were the primary constituents of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoid content of juice from C. aurantium is about one-fifth the flavonoid content of grapefruit juice (Edwards and Bernier, 1996). Okada et al (2017) have shown that an ethanol extract of bitter orange (dried immature fruit) induced expression of cytochrome CYP3A4 and P-glycoprotein in LS180 cells in culture by upregulating pregnane X receptor. Naringin and narirutin were the primary constituents of the extract.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that water extract of FA immature increased CYP3A4 protein expression and ethanol extract of FA immature induced CYP3A4 expression via induction of PXR expression ( Okada et al, 2017 ). They speculated that narirutin might be the key constituent increasing PXR expression and CYP3A4 protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the amount of these ingredients in AFI and AF vary depending on the harvesting time and geographical distribution. These flavonoids are believed to be major bioactive ingredients and have been reported to have hepatoprotective effects [26]. The chemical structures of major flavonoids in AFI and AF are shown in Fig.…”
Section: Flavonoids In Aurantii Fructus Immaturus and Aurantii Fructusmentioning
confidence: 99%